Happiness and Wellness - Biopsychosocial and Anthropological Perspectives 2023
DOI: 10.5772/intechopen.106771
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Happiness in the Pacific Islands: A Qualitative Study with University Staff in Fiji

Abstract: The concept of happiness has been the subject of critical analysis throughout the Western philosophical thought. Current conceptualizations focus on the role of cultural traditions and consumerist societal values. However, there is increasing scientific evidence that happiness is a product of multiple factors, the specific pattern of which differs across cultures. Yet, the cross-cultural literature tends to condense this into a Western–individualist versus non-Western-collectivist happiness dichotomy. This ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Alongside the extensive evidence indicating the negative impact of climate change on mental health, there is increasing literature suggesting the positive association between pro-environmental behaviour and subjective well-being. To begin with, recent research has shown that the natural environment emerges as a critical component of well-being and identity for people in the PICs (Crookes & Warren, 2022c). As such, concrete and proactive environmental behaviours could be construed as a pursuit of well-being.…”
mentioning
confidence: 99%
“…Alongside the extensive evidence indicating the negative impact of climate change on mental health, there is increasing literature suggesting the positive association between pro-environmental behaviour and subjective well-being. To begin with, recent research has shown that the natural environment emerges as a critical component of well-being and identity for people in the PICs (Crookes & Warren, 2022c). As such, concrete and proactive environmental behaviours could be construed as a pursuit of well-being.…”
mentioning
confidence: 99%